(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless sensor network is energy constraint network. The lifetime of a network is defined by the life of first specified percentage of dying nodes. Load balancing is a method to equalize energy consumption of all nodes and this way all nodes will degrade together. By load balancing, the lifetime of the network does not depend only on the life of weak node but depends on the life all nodes in the network which helps to increase the life of the network. In this paper, a distributed multi-hop routing algorithm for Load Balancing of Intermediate Nodes (LBIN) has been proposed to extend network lifetime. The objective of the proposed protocol is choose forwarded node in such a way, so they deplete their energy at approximately the same time, which is achieved by addressing the load balance problem at the node levels. At the node level, a predefined threshold is used to select the best node to balance the load in the selected subregion. This approach is shown to be an effective solution for load balancing and extending network lifetime in large multi-hop networks. This paper shows that the use of LBIN offers significant improvement over existing protocols in extending network lifetime.